Opinions and attitudes of women towards breastfeeding - Bień, Agnieszka; Kozak, Agnieszka; Rzońca, Ewa; Stadnicka, Sabina Katarzyna (Journal of Education, Health and Sport, 2017)
Introduction. Breast milk constitutes the integral part of feeding schedule of infants for the first year of their lives or even longer. According to recommendations of American, The ESPHAGAN Committee on Nutrition and The World Health Organization breastfeeding ought to be an exclusive way of infant feeding for the first six months of their lives. The aim of the study was to assess the attitudes of women towards breastfeeding and sociodemographic factors influencing these attitudes. Material and method. The research has been conducted among 262 women found in the following hospital wards: the pathology of pregnancy and the obstetrics and neonatal wards. The instrument of our research was our own survey questionnaire and the Iowa Infant Feeding Attitude Scale. Results. The average result of The Iowa in the studied group is 66,72 (±8,75).The highest results refer to the following statements: ‘breastfeeding strengthens the bond between an infant and its mother’ (4,70±0,78), ‘breast milk is ideal nourishment for infants’ (4,67±0,74) and ‘breast milk is cheaper than artificial milk’ (4,54±0,92). Married women showed more positive attitude towards the issue of breastfeeding (p=0,004). Two other groups with the above inclination make the women who had one child (p=0,044) and those who breastfed their children for two years (p=0,000). Conclusions. The most positive beliefs related to breastfeeding refer to the special relation between an infant and its mother, the belief that breastfeeding is an ideal solution for a baby and the appreciation of its economical aspect. Women are aware of the fact that breastfeeding is a challenge for them. Two main factors influence their opinion: the age of women and the number of births.